Efektivitas Pelaksanaan Pembelajaran Ditinjau dari Aspek Kemandirian Belajar Mahasiswa Program Guru Dalam Jabatan Prodi PG-PAUD FKIP Untan Pontianak - Desni Yuniarni; Halida . (Guru Membangun, 2013)
Education plays an important role in human life aspect. Therefore, people are required to be more creative and independent in developing education. The teacher of early age education in one of the important components in educating the Indonesia children to become a real person. Teachers have a role in the process of early age education, particularly in guiding children toward maturity, and independence. Hence, the teacher can be said as a spearhead of education in developing the real Indonesian. The role and position of teachers are strategic in preparing the qualified human resources for globalization era. It is also in line with the policy of development that put human resources as national development priorities. The improve the quality of learning, the teachers of early age education who attends the lecture is expected to be task asigned by lecturer.Keywords: efektivity, independen, teacher, early childhood education